Sex differences in the relationship between axial length and dry eye in elderly patients - Ayaki, Masahiko; Torii, Hidemasa; Yotsukura, Erisa; Negishi, Kazuno (Frontiers in Medicine, 2023)
Purpose: The aim of this study was to explore the association between myopia and dry eye (DE)-related ocular parameters. Methods: We recruited a total of 460 patients (mean age 73.6 y, 40.2% male) and performed DE-related, axial length (AL) and retinal examinations. Statistical analysis revealed a significant sex difference in AL, tear break-up time, strip meniscometry value, corneal staining score, corneal endothelial cell density, ganglion cell complex (GCC) thickness, peripapillary nerve fiber layer (NFL) thickness, and full macular thickness. AL was strongly age- and sex-dependent, so subsequent analyses were stratified by sex. Results: Among DE-related parameters, strip meniscometry value (ß=-0.167, p=0.033) and corneal endothelial cell density (ß=-0.139, p=0.023) were correlated with AL in women but not in men. Regarding retinal parameters, GCC thickness and full macular thickness were correlated with AL in women but not in men. Conclusion: The current results suggest a relationship of tear production and AL in elderly women and support the hypothesis that there may be a common upstream factor including the parasympathetic nervous system in the association between tear production and AL, or DE and myopia.